Analytical modeling of rotor-structure coupling using modal decomposition for the structure and the blades - Rouchon, T.; Cranga, P.; Malbert, F.; Roucoules, L. (My University, 2014)
This paper presents a linear semi-analytical model that is able to predict complex rotor-structure coupling phenomena and their stability. It was primarily designed so as to gain a better physical understanding of this kind of aeroelastic instabilities, triggering at higher frequencies than air and ground resonance, and involving several blade and structure modes. The analytical approach has a two-fold advantage since fast parametric studies can be carried out and a term-by-term analysis of the helicopter stability equations can be performed. In order to represent the elasticity of the structure and the blades, a modal decomposition method is introduced. The modal basis for the structure can either be obtained by a Finite Element Method or rigid degrees of freedom can be inputted. For the blades, a preliminary finite element routine is run, allowing for varying characteristics along the span. Blade offsets are introduced, and an unsteady aerodynamic model is implemented. The modal basis of the coupled system is then computed and a partial validation is done with HOST (Helicopter Overall Simulation Tool), a comprehensive aeroelastic code. Except for the built-in twist and the non-circulatory terms which are taken in a different manner in HOST and the presented model, the linearization results are similar. Future work using this model includes investigation of the helicopter stability thanks to parametric studies.